Investigation of VOC emissions from indoor and outdoor painting processes in shipyards - Celebi, Ugur Bugra; Vardar, Nurten (PERGAMON-ELSEVIER SCIENCE LTD, 2008)
Volatile organic compounds (VOCs) from painting solvents are one of the most important Sources of pollutant outputs for the shipbuilding and ship repair industry. Two ships of equal tonnage with the same painted area as each other, which were built in Turkish shipyards, are compared in terms of VOCs produced during painting and coating. Total area of all painted surfaces and total paint consumption of a 3500 deadweight tonne (DWT) oil/chemical tanker and a general cargo ship are calculated. An improved model for calculating the surface emissions of VOCs from painting and coating processes is utilized. Material balance emission estimation approach is employed to calculate the amount of VOCs, since it is used most often where a relatively large amount of material is emitted during use, and/or all air emissions are uncaptured. For both ships calculated VOCs are presented in figures. For the years 2005 and 2006 the total deadweight tonnage of ships delivered in Tuzla region, where 42 shipyards are located, is known. Therefore, a linear estimation is made to guess the total annual VOC emissions caused by painting operations. Finally, this information is used to project the total amount of VOCs emitted to the atmosphere for the year 2010. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: pollution sources; volatile organic compounds (VOCs); shipbuilding and ship repair industry; indoor and outdoor painting; Turkey; Environmental Sciences & Ecology; Meteorology & Atmospheric Sciences